(untitled) (Journal of Hama University, 2021)
The evaluation of the results of clinical training in dental work is of great importance in identifying problems and trying to avoid them in the future. Therefore, this study was to assess Assessment of students’ knowledge of the College of Dentistry of the detailed stages of restorations of dental amalgam in children, which is a cross-sectional study that included 200 students in the fourth and fifth years and postgraduate studies in the Department of Pediatric Dentistry. The general assessment was made based on the method of restoration by dental amalgam and detailed according to Macdonald & Avrey 2016 . Information was collected from forms that were distributed electronically and were filled out, then after 10 days the questionnaire was redistributed and the same individuals were asked to re-fill it to compare the responses, and a Kappa test was conducted to check the reliability of their responses, and it reached a value of 0.81. The questionnaire consists of 14 questions, the questionnaire contains two parts: in the first section Data were collected on students (gender - educational stage), and the second section included questions about the details of the stages of applying dental amalgam from preparing the predicate until removing it. The questionnaire was sent to 200 individuals via e-mail for a month and the data was collected after signing the informed consent attached to the questionnaire. Of 166 participants, a response rate of 83%, 65% for fourth-year students, 30% for fifth-year students, and 5% for postgraduate students, The percentage of those who use the rubber barrier during the restoration was 43%, and by 67% to use the MOD, and the majority of 57% do not make sure of the width of the post when applying, noting that the problems of application of the support are concentrated after the stability of 31% and the increased height of the support strip is 32%, and a high percentage of the knowledge of the application was noticed. The vestibule of the backing is 88%, but with a lack of knowledge of the stages of polishing and sculpting in general, and a lack of knowledge of methods for examining plates after completion, and thus the stages of carving and polishing amalgam and methods of examining dishes formed the clearest weaknesses of students and practitioners of dental amalgam restorations on temporary molars.